2012
DOI: 10.1029/2011ja017293
|View full text |Cite
|
Sign up to set email alerts
|

Radio occultation measurement of the electron density near the lunar surface using a subsatellite on the SELENE mission

Abstract: [1] The electron density distribution in the vicinity of the lunar surface was explored with the radio occultation technique using a subsatellite on the SELENE mission. Although the measurements suffer from contamination by the terrestrial ionosphere and interplanetary plasma, an analysis of more than 300 measurements provides adequate statistics and reveals a general trend. The result suggests that a dense ionosphere covering the whole sunlit side, as suggested by the radio occultation measurements on the Sov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 24 publications
(35 reference statements)
3
16
0
Order By: Relevance
“…A linear fit was then applied to the first 2 min of Doppler residual data prior to occultation, and the fit was extended for last 1 min of the observations. It is worth mentioning that similar electron density profiles were obtained using Selene RO measurements [Imamura et al, 2012] as well. Only if the phase changes during the occulted period exceeded one sigma of the fluctuation during first 2 min, we assumed that the extra phase change in the signal was due to occulted lunar ionosphere.…”
Section: Radio Occultation Measurementssupporting
confidence: 74%
See 2 more Smart Citations
“…A linear fit was then applied to the first 2 min of Doppler residual data prior to occultation, and the fit was extended for last 1 min of the observations. It is worth mentioning that similar electron density profiles were obtained using Selene RO measurements [Imamura et al, 2012] as well. Only if the phase changes during the occulted period exceeded one sigma of the fluctuation during first 2 min, we assumed that the extra phase change in the signal was due to occulted lunar ionosphere.…”
Section: Radio Occultation Measurementssupporting
confidence: 74%
“…This experiment presented an evidence for the existence of a thin ionosphere around Moon with a density of the order of 10 2 cm −3 . Radio occultation of the Moon's ionosphere by SMART 1 has also shown the existence of ionosphere with columnar density of the order of 10 13 el/cm 2 [Pluchino et al, 2008] which was further confirmed by the Selene RO measurements [Imamura et al, 2012]. The estimated columnar density of the lunar ionosphere was in the range of 3-5 × 10 14 el/cm 2 .…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…The nominal observation mode of the SELENE radio occultation experiment, which used a single spacecraft, covered a considerably wider SZA range. The results obtained with this observation mode suggest a weak electron density enhancement with densities on the order of 100 cm −3 below 30 km altitude at solar zenith angles less than 60° [ Imamura et al , 2012]. Although the classical ionosphere generation mechanism does not seem to work near the lunar surface, photoelectron emission from exospheric dust particles is promising.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent experiment with LRS (Lunar Radio Science) on Kaguya‐SELENE by the Japanese space agency has found evidence of transient enhancements in surface electron density around 250/cm 3 but only within a solar zenith angle of 60°. They used radio occultation experiments with multiple spacecraft to probe the lower lunar atmosphere (Imamura et al, ). SELENE did not find a large persistent enhancement like Luna over the whole dayside.…”
Section: Noisementioning
confidence: 99%